Hiccups induced by aripiprazole combined with sertraline in an adolescent with olfactory reference disorder: A case report - Li, Zhe; Xiong, Zhenzhen; Jiang, Xingmei; Li, Zhixiong; Yuan, Yiwen; Li, Xiao (Frontiers in Psychiatry, 2022)
Background: Hiccup can cause significant distress to patients and affect medication compliance. Individuals with olfactory reference disorder (ORD) who might develop persistent hiccups when treated with a combination of antidepressant and antipsychotic, leading to significant distress and impairment. Case summary We report a rare case of an adolescent with ORD who was treated with aripiprazole combined with sertraline and who began to hiccup persistently after 6 days on this treatment. He stopped hiccupping after the aripiprazole had been suspended for 12 h. After discharge, the patient continued on sertraline alone and reported no hiccupping at 1-month follow-up. Conclusion Clinicians should consider that the combination of aripiprazole and sertraline can induce hiccups during the acute administration period in adolescents with ORD.